Total Moral Quality: A New Approach for Character Education in Pesantren - Hasan Baharun (Ulumuna, 2017)
This paper presents the concept of character education in pesantren which gives valuable contributions to the success of moral development for students. It also offers a different paradigm in developing the concept of character building in educational institution. This article is inspired by the lack of effective character learning in a variety of formal educational institutions. Hence, the schools which succeed in instilling character education can be used as a reference to develop character education. This study focuses on character education model developed by pesantren and offers an alternative perspective of the development of character education in Indonesia. This study adopts a qualitative research approach and uses a case study design. The study shows that the model of character education in pesantren is carried out through a multi-disciplinary approach so as to provide maximum results for the development of character education. This study suggests that the Total Moral Quality (TMQ) is the further development of Thomas Lickona’s concept of character education of moral modeling, moral knowing, moral feeling and moral habituation and is applicable in the school.